Effects of Steel and Glass Fibers on the Compressive Behavior of Rubberized Concrete: An Experimental Study and Constitutive Modeling - Hongjie Lv; Lijuan Li; Weiping Zhu; Xiaohui Li; Daochu Wang; Zao Ling; Pandeng Feng; Feng Liu (Buildings, 2024)
Rubberized concrete exhibits enhanced toughness and sustainability but suffers from reduced mechanical strength, limiting its applications. This study enhanced the compressive strength of rubberized concrete using hybrid steel/glass fibers. The results showed a positive synergy between the hybrid fibers, with improvements in compressive strength, elastic modulus, Poisson’s ratio, peak strain, and compressive toughness by 16.1%, 19.4%, 32.0%, 63.4%, and 101.7%, respectively, at a hybrid fiber content of 0.8% (steel fiber 0.6% and glass fiber 0.2%). A well-fitting stress–strain model was adopted for future constitutive simulations. This study advances the understanding of rubberized concrete with hybrid steel/glass fibers under axial compression and promotes its application in structural engineering.